Acute effect of passive rest intervals and stretching exercise on multiple set performance - Antonio Claudio do Rosário Souza; Carmen Lúcia Borges Bastos; Maria de Nazaré Dias Portal; Belmiro Freitas de Salles; Thiago Matassoli Gomes; Jefferson da Silva Novaes (Universidade Federal de Santa Catarina, 2009)
The objective of this study was to determine the acute effect of passive rest intervals and static stretching between resistance exercise sets on the number of maximal repetitions (RM), rating of perceived exertion (RPE), and cumulative number of repetitions in multiple sets with a workload adjusted by the 8RM test. Fourteen trained male subjects (24.4 ± 2.1 years; 79.1 ± 7.1 kg; 175.4 ± 5.6 cm) were studied. On the first two visits, the subjects were submitted to the test and 8RM re-test using chest press (CP) and squat (SQ) exercises. On the two subsequent visits, all subjects were randomly assigned to two experimental situations: a) 8RM test with a passive rest interval (PI); b) 8RM test with static stretching (SS). The subjects performed three sets of CP and SQ, intercalated with 2 minutes of passive rest or 30 seconds of static stretching. ANOVA revealed a significant decrease (p < 0.05) in the second (PI = 6 ± 0.8 x SS = 5.2 ± 1.0 repetitions) and third (PI = 4.1 ± 0.8 X SS = 3.3 ± 0.6 repetitions) sets for CP and only in the third set (PI = 4.9 ± 0.8 X SS = 4.2 ± 1.0 repetitions) for SQ. For RPE, the Wilcoxon test showed significant differences (p < 0.05) between all sets for CP and SQ. For the cumulative number of repetitions, the paired t-test revealed a significant decrease (p < 0.05) for CP (PI = 18.3 ± 1.5 X SS = 16.8 ± 1.6 repetitions). These results indicate that static stretching between resistance exercise sets decreases 8RM test performance.